2018
DOI: 10.3382/ps/pey012
|View full text |Cite
|
Sign up to set email alerts
|

Forsythia suspensa extract attenuates breast muscle oxidative injury induced by transport stress in broilers

Abstract: This experiment was conducted with 144 male Arbor Acre broilers (one d old, weighing 45.6 ± 1.3 g) to determine protective effects of Forsythia suspensa extract (FSE) against breast muscle oxidative injury induced by transport stress (TS). The birds were randomly allotted to one of 4 treatments in a 2 × 2 factorial arrangement. The treatments consisted of broilers fed diets supplemented without or with FSE (100 mg/kg) and challenged without or with TS for 3 h before slaughter. Transport stress increased live B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 58 publications
5
27
1
2
Order By: Relevance
“…F. suspensa extracts might also be beneficial to alleviate growth inhibition and immune damage of broilers under heat stress and corticosterone stimulation ( Zeng et al., 2014 , Zhao et al., 2017b ). Previous studies in our laboratory also reported FSE could reduce transport stress, slow down muscle protein degradation and growth inhibition, and improve muscle antioxidant capacity and meat quality in broilers ( Pan et al., 2018a , Pan et al., 2018b ). However, to the best of our knowledge, few studies focus on the possible role for FSE in replacing antibiotics under nonchallenge conditions and the possible mechanism on improvement of performance in broilers.…”
Section: Introductionsupporting
confidence: 58%
See 3 more Smart Citations
“…F. suspensa extracts might also be beneficial to alleviate growth inhibition and immune damage of broilers under heat stress and corticosterone stimulation ( Zeng et al., 2014 , Zhao et al., 2017b ). Previous studies in our laboratory also reported FSE could reduce transport stress, slow down muscle protein degradation and growth inhibition, and improve muscle antioxidant capacity and meat quality in broilers ( Pan et al., 2018a , Pan et al., 2018b ). However, to the best of our knowledge, few studies focus on the possible role for FSE in replacing antibiotics under nonchallenge conditions and the possible mechanism on improvement of performance in broilers.…”
Section: Introductionsupporting
confidence: 58%
“…The current results might be due to the main ingredients of FSE as natural antioxidants could activate the antioxidant defense system ( Lee et al., 2000 ) and Nrf2 system ( Jung and Kwak, 2010 ) in cell membranes of tissues. The improved antioxidant status of broilers fed FSE might also be due to the fact that the FSE could lower DPPH radical-scavenging activity and MDA content ( Lu et al., 2010 , Pan et al., 2018a ). In addition, the results could also be due to the antioxidant effects of forsythiaside A in FSE, which could improve antioxidant capacity in vitro ( Lu et al., 2010 ) and in vivo ( Zhao et al., 2017a ) via the enhancement of gene expression of antioxidant enzymes in cells ( Cheng et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A high concentration of urea-N in serum is a risk indicator of cardiovascular diseases, whereas the low concentration of uric acid has protective effects on oxidative stress in body ( Glantzounis et al., 2005 ). In addition, the higher concentration of urea nitrogen in serum was reported as transport stressor in broilers ( Pan et al., 2018a , b ).…”
Section: Discussionmentioning
confidence: 99%